2009
DOI: 10.1248/jhs.55.215
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Donepezil on Vascular Endothelial Dysfunction-Associated Dementia Induced by L-Methionine in Rats

Abstract: Donepezil (acetyl cholinesterase inhibitor) is a mainstay of clinical intervention to contain memory deficits of Alzheimer's disease. However, its beneficial role in endothelial dysfunction-associated dementia i. e. vascular dementia still needs to be explored. The present study was designed to investigate the effect of donepezil on vascular endothelial dysfunction, and associated memory deficits in rats. Atorvastatin (3-hydroxy-4-methyl-glutaryl (HMG)-CoA inhibitor) was taken as the standard. Rats were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 54 publications
4
11
0
Order By: Relevance
“…Earlier literature on donepezil suggests that in addition to its usefulness in dementia of Alzheimer's disease, it also exerts a beneficial effect in different animal models of VaD (Koladiya et al 2009;. Present study data with donepezil, as positive control, is in concurrence with earlier reports from another laboratory .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Earlier literature on donepezil suggests that in addition to its usefulness in dementia of Alzheimer's disease, it also exerts a beneficial effect in different animal models of VaD (Koladiya et al 2009;. Present study data with donepezil, as positive control, is in concurrence with earlier reports from another laboratory .…”
Section: Discussionsupporting
confidence: 91%
“…for 32 days) to induce HHcy-associated endothelial dysfunction and VaD (Shah & Singh 2007;Koladiya et al 2008Koladiya et al , 2009). …”
Section: Induction Of Hhcy and Edmentioning
confidence: 99%
“…Endothelial dysfunction has also been reported to be related to higher oxidative stress levels (Javeshghani et al 2009;Ozkul et al 2010;Weseler and Bast 2010). Moreover, in our earlier studies, we have demonstrated that vascular endothelial dysfunction in addition to impairment of memory and oxidative stress produces rise in brain AChE activity (Koladiya et al 2008(Koladiya et al , 2009. Furthermore, very recently we have reported that single diabetogenic dose of STZ produces vascular dementia manifested in terms of endothelial dysfunction, memory impairment as well as brain oxidative stress and rise in brain AChE activity of rats.…”
Section: Discussionmentioning
confidence: 52%
“…Acetylcholinesterase inhibitors are the main class of drugs which are frequently used for the management of memory deficits. In our previous reports, we have demonstrated that donepezil, in addition to its usefulness in dementia of AD , also exerts a beneficial effect in different animal models of vascular dementia (Koladiya et al 2008(Koladiya et al , 2009Sharma and Singh 2010). Donepezil is already in clinical use for management of dementia of AD, and hence in the present study it has been used as a positive control.…”
Section: Discussionmentioning
confidence: 90%
“…Endothelial dysfunction (vascular defects) has also documented to be related to higher oxidative stress levels [53][54][55]. Further, vascular defects have also been reported to produce rise in brain AChE activity [24,56]. Therefore, the noted memory impairment and various biochemical abnormalities in this study are probably linked to STZ diabetes induced endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 65%